2015
DOI: 10.1123/ijgs.2015-0009
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of an Eight-Week Plyometric Training Program on Golf Swing Performance Characteristics in Skilled Adolescent Golfers

Abstract: The purpose of this study was to determine the effects of an eight-week plyometric training 2 intervention on measures of golf swing performance in highly skilled, adolescent golfers. Sixteen 3 male golfers were recruited to this study, being placed into two handicap and age-matched groups: 4 intervention and control. The intervention group completed an eight-week plyometric training 5 programme in addition to their golf-specific practice to study effects on clubhead speed (CHS), ball 6 carry distance (BCD) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 5 publications
1
10
1
Order By: Relevance
“…However, it should be noted that there was an extremely small sample size (n 5 6), which again somewhat prevents the findings from being extrapolated to other female players. Furthermore, given the low sample size and the fact that golf is an individual sport, it would have been useful to have some individual data analysis conducted (e.g., are changes in CHS greater than each athlete's own measurement error), which has been conducted previously in male studies (6,45). This study also aimed to determine the effects on putting distance control, which showed noticeably smaller changes postintervention.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that there was an extremely small sample size (n 5 6), which again somewhat prevents the findings from being extrapolated to other female players. Furthermore, given the low sample size and the fact that golf is an individual sport, it would have been useful to have some individual data analysis conducted (e.g., are changes in CHS greater than each athlete's own measurement error), which has been conducted previously in male studies (6,45). This study also aimed to determine the effects on putting distance control, which showed noticeably smaller changes postintervention.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the continued interest in long-term athletic development (15), the need for national governing bodies to identify and develop young prospective players (28), and the beneficial effects that resistance training offers to sport-specific performance (14), there is a distinct lack of research that has investigated the effects of strength and conditioning interventions on golf swing performance in youth golfers. To the best of our knowledge, only 4 studies have investigated the effects of resistance training interventions on golf swing performance in junior-level golfers (2,5,27,31). Although all 4 interventions showed increases in physical fitness (e.g., strength, power, or mobility) and golf swing performance (e.g., CHS, ball speed, and handicap), none of the studies considered maturation within their analyses, despite one of the studies measuring maturity status (27).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has predominantly used simple performance metrics such as jump height to assess physical fitness, which typically fail to provide practitioners with insights into the kinetic changes underlying training-induced adaptations. Of the available evidence, countermovement jump (CMJ) height has typically been used to reflect lower-limb power (2,5,27); however, as a standalone measure, CMJ height does not provide insight into the underpinning kinetic strategies. Similarly, muscular strength has been assessed through a single-leg progressive squat depth test (31) and modified push-ups (5), with both tests not reflecting maximal force production, which has been identified as one of the strongest predictors of 6-iron and driver CHS in youth (30) and adult golfers (36,37).…”
Section: Introductionmentioning
confidence: 99%
“…The crossover from the EMG evidence (24) to the muscles involved in the OHS may imply that increases in the strength and flexibility of specific muscles could influence the kinematics of the swing. Various studies have analyzed the effect of exercise interventions on the outcome measures of the golf swing (e.g., clubhead speed [CHS] and ball speed [BS]), with both home-and gym-based programs prescribed (5,14,16,23,29). Intervention session frequency ranged from once per week (55% adherence over a 7-week period (29)) to 3-4 sessions per week (for an 8-week period (23)).…”
Section: Introductionmentioning
confidence: 99%